A intencionalidade na escrita argumentativa do ensino médio: do planejamento ao texto - Oliveira, Michele Mendes Rocha de (2022)
This Doctor’s research aims to investigate how working with the textual principle of intentionality helped in producing argumentative texts by students of the 2nd year in high school at Colégio Militar de Santa Maria. In order to embody this action research, we chose the genre argumentative chronicle. Text studies from this genre are centered on the precepts of Text Linguistics, especially in Beaugrande and Dressler (1981) with regard to intentionality, and in Koch (2014; 2015; 2016), and Jubran (2015) regarding topical progression and articulators. For the foundations on text plan, we used Adam (2011), Cabral (2013), Marquesi, Elias and Cabral (2017), while metacognition was based on studies by Flavell (1976; 1979) and Gerhardt (2017). Other authors that also support this research are White and Arndt (1991) regarding process writing; Ruiz (2015) on interactive textual evaluation; Freire and Faundez (2017) for problematizing questions. As for the didactic sequence, we turn to Dolz and Schneuwly (2004). With regard to methodological basis on action research, we have Burns (1999), Carr and Kemmis (1988), and Thiollent (2011). The didactic sequence was worked with the students between the months of April and November 2019, so that the project covered all the students in the class. The analysis was carried out from the productions of a subject. The results reveal the contribution of the work with intentionality through the conscious use of textual articulators, the organization of ideas through topical progression, and the elaboration of the text plan permeated by metacognitive activities. The contribution was made not only regarding the qualification of the student’s text, but, above all, regarding the awareness of her intentionality and the metacognitive processes of learning. Thus, we notice that the tasks of producing argumentative texts at school need to encompass the work with the intentionality so that from planning to writing the final version there is the development of awareness about the linguistic resources, with the development of the students’ autonomy regarding their learning process.